Gelatin/Poly (Lactic-Co-Glycolic Acid)/Attapulgite Composite Scaffold Equipped with Teriparatide Microspheres for Osteogenesis in vitro and in vivo - Zhao Z; Feng X; Zhao Y; Song Z; Zhang R; Zhang K; He Y; Chen G; Zhang J; Wang W (International Journal of Nanomedicine)
Zhenrui Zhao,1 Xiaofei Feng,1 Yuhao Zhao,1 Zhengdong Song,1 Ruihao Zhang,1 Kui Zhang,1 Yixiang He,1 Guoliang Chen,1 Jing Zhang,2 Wenji Wang3 1Department of Orthopedics, The First Clinical Medical College of Lanzhou University, Lanzhou, People’s Republic of China; 2Department of Orthopedics, Anlu People’s Hospital, Anlu, People’s Republic of China; 3Department of Orthopedics, the First Hospital of Lanzhou University, Lanzhou, People’s Republic of ChinaCorrespondence: Wenji Wang, The First Hospital of Lanzhou University, Lanzhou, 730000, People’s Republic of China, Tel +8613893221698, Email wwjldyy@163.comBackground: Given the risks associated with autologous bone transplantation and the limitations of allogeneic bone transplantation, scaffolds in bone tissue engineering that incorporate bioactive peptides are highly recommended. Teriparatide (TPTD) plays a significant role in bone defect repair, although achieving controlled release of TPTD within a bone tissue engineering scaffold remains challenging. This work reports a new approach for treatment of teriparatide using a water-in-oil-in-water (w/o/w) microspheres be equipped on gelatin (GEL)/Poly lactic-glycolic acid (PLGA)/attapulgite (ATP) scaffold.Methods: In this study, TPTD microspheres were prepared by the water-in-oil-in-water (w/o/w) double emulsion technique and GEL/PLGA/ATP composite scaffolds with different setups were prepared by salt leaching method. Both microspheres and scaffolds underwent physicochemical characterization. Mouse bone mesenchymal stem cells (BMSCs) were co-cultured with extracts from the microspheres and scaffolds to evaluate cell proliferation and osteogenesis. Four weeks post-implantation, the effectiveness of the scaffolds containing microspheres for repairing skull defects in mice was assessed.Results: Both TPTD microspheres and the GEL/PLGA/ATP scaffold significantly enhanced the proliferation and osteogenic differentiation of BMSCs. Markers of osteoblast activity, including COL1, RUNX2, OCN, and OPN, were markedly up-regulated. Further, micro-CT, histological, and immunohistochemical analyses revealed extensive new bone formation on the scaffold.Conclusion: The GEL/PLGA/ATP composite scaffold, equipped with TPTD microspheres, demonstrates significant potential for use in bone tissue engineering, providing an effective option for bone regeneration and repair in clinical applications. Keywords: teriparatide, microsphere, gelatin, PLGA, attapulgite, bone tissue engineering, bone defect, bone regeneration